2021
DOI: 10.1111/ejn.15433
|View full text |Cite
|
Sign up to set email alerts
|

The cross‐talk between RAGE and DIAPH1 in neurological complications of diabetes: A review

Abstract: Neuropathy, or dysfunction of peripheral nerve, is one of the most common neurological manifestation in patients with diabetes mellitus (DM). DM is typically associated with a hyperglycaemic milieu, which promotes non‐enzymatic glycation of proteins. Proteins with advanced glycation are known to engage a cell‐surface receptor called the receptor for advanced glycation end products (RAGE). Thus, it is reasonable to assume that RAGE and its associated molecule‐mediated cellular signalling may contribute to DM‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 118 publications
(330 reference statements)
0
25
0
Order By: Relevance
“…On staining the Bergmann glia with S100β, we did not see increased immunoreactivity in Bergmann glia or proliferation of Bergmann glia (figure 5C,F), but we did observe a strong trend of increased S100β reactivity in the IGL extracellular space (figure 5D,E). S100β is known to be secreted during metabolic stress and functions via binding to a receptor of advanced glycation end products 56 57. Overall, this finding suggests that CASK loss-of-function produces protracted neuronal loss in the cerebellum, explaining why MICPCH in humans typically becomes obvious a few months after birth.…”
Section: Resultsmentioning
confidence: 91%
“…On staining the Bergmann glia with S100β, we did not see increased immunoreactivity in Bergmann glia or proliferation of Bergmann glia (figure 5C,F), but we did observe a strong trend of increased S100β reactivity in the IGL extracellular space (figure 5D,E). S100β is known to be secreted during metabolic stress and functions via binding to a receptor of advanced glycation end products 56 57. Overall, this finding suggests that CASK loss-of-function produces protracted neuronal loss in the cerebellum, explaining why MICPCH in humans typically becomes obvious a few months after birth.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, DIAPH1 is required as a RAGE bridging protein for active signaling and molecular pathways in a variety of vascular and inflammatory cells, such as endothelial cells, smooth muscle cells, and macrophages (3,99,100). Evidence suggests that the interaction of ctRAGE with DIAPH1 is critical for intracellular signaling such as AKT phosphorylation and the JAK/STAT signaling cascade (101)(102)(103). (Figure 1).…”
Section: Rage-mediated Signaling Pathwaysmentioning
confidence: 99%
“…In addition, increased expression of HMGB1 and RAGE in diabetic peripheral neuropathy (117). The interaction analysis using GeneMANIA software suggests that HMGB1-RAGE-DIAPH1 interaction may be critical for the progression of diabetic peripheral neuropathy (103).…”
Section: Rage and Diabetes Complicationsmentioning
confidence: 99%
“…[9][10][11] Moreover, the S100B is present in the serum of patients with diabetes; hence, RAGE-S100B cross-talk may play a crucial role in the progression of DLDN. [6][7][12][13][14] Consequently, our previous studies revealed that the expression of S100B protein was elevated in porcine hyperglycemic sciatic nerve. 12 However, recent data on DLDN pathogenesis have revealed that another player, diaphanous-related formin 1 (DIAPH1) [7][8][9][10][11][15][16] , an intracellular cytoplasmic ligand of RAGE, might be involved.…”
Section: Introductionmentioning
confidence: 98%
“…Until now, evidence indicated that a variety of factors, such as local neuroinflammation, malfunctions in cytoskeleton remodeling, impaired axonal transport, and enhanced oxidative stress, might be involved in the progression of LDN in patients suffering from diabetes. [6][7][8][9][10][11] Advanced glycation end products (AGEs) are the products of nonenzymatic glycation and oxidation of proteins and lipids. AGEs may accumulate in different biological locations, such as the peripheral nervous system (PNS).…”
Section: Introductionmentioning
confidence: 99%